2020
DOI: 10.1063/5.0023722
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of spin–orbit interaction in epitaxially grown InAs nanosheets

Abstract: We report on a low-temperature transport study of a single-gate, planar field-effect device made from a free-standing, wurtzite-crystalline InAs nanosheet. The nanosheet is grown via molecular beam epitaxy and the field-effect device is characterized by gate transfer characteristic measurements and by magnetic field orientation dependent transport measurements. The measurements show that the device exhibits excellent electrical properties and the electron transport in the nanosheet is of the twodimensional nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…A theoretical study predicted that although it is natural to grow n-type Bi2O2Se, as-grown Bi2O2Te without doping should behave as an intrinsic semiconductor. 28 Figure 1(c) shows the measured longitudinal resistance 𝑅𝑅 xx and Hall resistance 𝑅𝑅 yx of our Bi2O2Te Hall-bar device at perpendicularly applied magnetic fields B and at 𝑇𝑇 = 2 K and 𝑉𝑉 g = 0 V. It is seen that 𝑅𝑅 xx displays a well-defined dip at low fields, i.e., a typical WAL characteristc, 11,25 revealing the presence of a strong SOI in the Bi2O2Te nanosheet. Here we note that similar WAL characteristics are also observed in other Hall-bar devices fabricated from thicker Bi2O2Te nanosheets (see Supplementary Materials).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…A theoretical study predicted that although it is natural to grow n-type Bi2O2Se, as-grown Bi2O2Te without doping should behave as an intrinsic semiconductor. 28 Figure 1(c) shows the measured longitudinal resistance 𝑅𝑅 xx and Hall resistance 𝑅𝑅 yx of our Bi2O2Te Hall-bar device at perpendicularly applied magnetic fields B and at 𝑇𝑇 = 2 K and 𝑉𝑉 g = 0 V. It is seen that 𝑅𝑅 xx displays a well-defined dip at low fields, i.e., a typical WAL characteristc, 11,25 revealing the presence of a strong SOI in the Bi2O2Te nanosheet. Here we note that similar WAL characteristics are also observed in other Hall-bar devices fabricated from thicker Bi2O2Te nanosheets (see Supplementary Materials).…”
mentioning
confidence: 92%
“…Here, due to the fact that the device is made in a single-gate structure, it is hard to achieve a sufficiently large tuning of the electric field in the nanosheet. 11,25 The extracted 𝐿𝐿 e is ~8 nm and is also weakly dependent on Vg. This extracted value of 𝐿𝐿 e is consistent with the results determined above from the carrier density and mobility measurements shown in Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Low-dimensional III-V narrow bandgap semiconductor nanostructures have attracted signicant interest due to their potential applications in nanoelectronics, 1,2 infrared optoelectronics, 3,4 spintronics, [5][6][7] and quantum electronics. [8][9][10][11][12][13] Among them, strong spin-orbit interaction (SOI) and large Landé gfactor have made InAs and InSb nanostructures widely used in realization of novel devices such as spin transistors, 14,15 spinorbit qubits, 16,17 and topological quantum devices. [18][19][20][21] The SOI originates from the nonrelativistic approach to the relativistic Dirac equation and describes that a moving (orbit) charged particle in an electric eld experiences an effective magnetic eld and thus the spin and momentum of the charged particle are coupled with the coupling strength being related to the electric eld.…”
mentioning
confidence: 99%
“… 28 The preliminary study has experimentally demonstrated the existence of strong SOIs in the nanosheets. 9 However, due to the employment of a single-gate device configuration, the study has failed to reveal the origin and an efficient control of the SOI in the InAs nanosheets.…”
mentioning
confidence: 99%